Determination of the effects on learning and memory performance and related gene expressions of clothianidin in rat models - Ozdemir, Hasan Huseyin; Kara, Murat; Yumrutas, Onder; Uckardes, Fatih; Eraslan, Ersen; Demir, Caner F.; Bal, Ramazan (Springer, 2014)
Clothianidin (CLO) is one of the pesticides used to protect against insects, and its potential toxic effects on cognitive functions are not clearly known. This study aims to evaluate the possible effects of dose-dependent CLO on learning and memory in infant and adult male rats and the expression of related genes in the hippocampus. Doses of 2, 8 and 24 mg/kg of CLO were administered to newborn infant and adult albino Winstar rats in the form of gavage and dissolved in vehicle matter. Their cognitive and learning functions were evaluated by the Morris water maze and probe tests. Expression levels of N-methyl D-aspartate 1 (GRIN1), muscuranic receptor M1, synoptophysin (SYP) and growth-associated protein 43 (GAP-43) of tissues isolated from the hippocampus were determined using the real-time PCR method. In the Morris water maze test, no change (p > 0.05) was exhibited in the adult and infant rats after CLO was applied, although there was a significant difference (p < 0.05) in performance between infants and the control group after 24 mg/kg was applied in the probe test. Also, expression levels GRIN1, M1, SYP, GAP-43 did not change when compared to the control (p > 0.05). Our study shows that exposure to high doses of CLO causes deterioration of cognitive functions in infant rats.
Keywords: Clothianidin; Cognitive function; N-methyl D-aspartate 1; Muscarinic receptor M1; Synoptophysin; Growth-associated protein 43